Development and Application of Single-wire-sliding-type Friction Tester for Cosmetics - Misaki, Eiichiro; Nonomura, Yoshimune; Kashimoto, Akio; Oshitani, Jun; Igarashi, Takanori (Funtai Kogakkaishi, 2007)
Pleasant feeling when using makeup cosmetics is an essential factor. Therefore, we have to pay attention to the physical properties of cosmetic powders, especially frictional property, but it is difficult to measure it without the skill of experts. We heve developed a friction tester, which measures the friction exerting on a wire when it is pulled out from the powder bed. The single-wire-sliding-type friction tester can readily measure the friction characteristic of powder while controlling the pressure acting on the bed. This tester had a high sensitivity with a good reproducibility. The frictional property of cosmetics materials like flake powder can be evaluated by the tester. For an example, we have tried to make the spray-dried powder containing Ca-LT in order to improve the rough touch of TiO2.